Gross Job Flows in Ukraine: Size, Ownership and Trade Effects - Jozef Konings; Olga Kupets; Hartmut Lehmann (Institute for the Study of Labor (IZA), 2003)
This paper documents and analyses gross job flows and their determinants in Ukraine using a unique data set of more than 2200 Ukrainian firms operating in both the manufacturing and the non-manufacturing sector for the years 1998-2000. There are several important findings in the paper. Job destruction is dominating job creation in both 1999 and 2000. In connection with other evidence we infer from this that Ukraine is only at the beginning of the restructuring process. The most clear-cut result of our analysis is the strong positive effect of new private firms on net employment growth, a finding established for other transition economies as well. At the same time, we do not find differences in the employment growth of state-owned and privatised firms. Apart from ownership effects we also find, at the firm level, an inverse correlation of size and net employment growth and of size and job reallocation. Finally, we establish that strong foreign trade links force firms to shed labour more aggressively and to engage in more restructuring when trade is directed to and originating from Western economies. This disciplining function is absent when the trade flows are confined to CIS countries.
Keywords: J63; F14; P23; E24; 330; job creation; job destruction; Ukraine; private firms; trade; Arbeitsmobilität; Beschäftigung; Reorganisation; Eigentümerstruktur; Außenhandelswirtschaft; Ukraine